Residual platelet reactivity after pre-treatment with ticagrelor prior to primary percutaneous coronary intervention is associated with suboptimal myocardial reperfusion. Issue 2 (12th August 2019) - Roule, Vincent; Heudel, Thibaut; Lemaitre, Adrien; Bignon, Mathieu; Ardouin, Pierre; Sabatier, Rémi; Blanchart, Katrien; Beygui, Farzin
Abstract: Background: The evidence of a clinical benefit of P2Y12 inhibitor pre-treatment in primary percutaneous coronary intervention (PCI) and the relation between the level of platelet inhibition and myocardial reperfusion with newer potent P2Y12 inhibitors remain unclear. We aimed to assess the relationship between platelet reactivity at the time of primary PCI after pre-treatment with aspirin and ticagrelor and the post-PCI myocardial blush grade (MBG). Methods: We prospectively included 61 patients. Platelet reaction units for ticagrelor (PRU) and aspirin reaction units (ARU) were measured using the point-of-care test VerifyNow before PCI. The high on-ticagrelor (PRU >208) and on-aspirin (ARU ⩾ 550) platelet reactivity (HPR and HaPR) were assessed. Patients were divided into two groups according to MBG 3 or <3. Results: MBG 3 was identified in 28 (46%) patients. Mean PRU was lower in such patients as compared with those with MBG <3 (155.82 ± 90.91 vs . 227.42 ± 65.18; p =0.001) while mean ARU was similar between groups. HPR and HaPR were observed in 30 (49.2%) and 11 patients (18%), respectively. HPR but not HaPR was more frequent in the group with impaired MBG (66.7 vs . 28.6%; p =0.003 and 21.2 vs. 14.3%; p =0.48 respectively). Conclusion: Our study shows that higher PRU and the subsequent HPR at the time of primary PCI, after pretreatment with ticagrelor, are the only correlates of post PCI MBG. These findings support the earliest possible loading with ticagrelor prior to primary PCI.